Sex Ratios, Polygyny, and the Value of Women in Marriage: A Beckerian Approach - Shoshana Grossbard-Shechtman (Institute for the Study of Labor (IZA), 2014)
A central component of his theory of marriage Becker's Demand and Supply (D&S) models of marriage are also among the most unique models he pioneered. Here I provide an overview of Becker's analysis of the effects of sex ratios the ratio of men to women in marriage markets on individual consumption of married men and women, and indicate some of the ways that this analysis has been expanded and tested. Becker also used D&S analysis to develop his argument that polygyny benefits women and used the positive association between brideprice and polygyny as evidence. Relying on D&S models of marriage and based on the section of Becker's Treatise on the Family dealing with "price" rigidities in marriage it is shown that polygyny may be harmful to women. Furthermore, the positive association between brideprice and polygyny does not necessarily prove that women are better off under polygyny than under monogamy.
Keywords: J12; J16; 330; economics of marriage; Gary Becker; sex ratios; bride price; polygyny